Manajemen Strategi Pemasaran Untuk Meningkatkan Daya Saing UMKM di Bekasi Pasca COVID-19 - Aspan Priana (Jurnal Riset Akuntansi, 2024)
In this research, MSME entrepreneurs are encouraged to develop their ability to develop marketing strategies so that they are able to manage knowledge that will move them to become more competitive and innovative in a business competition. The problems and solutions of MSME entrepreneurs in Bekasi towards the sustainability of their businesses are a form of steps that will be continued to maintain, improve and develop their businesses through strengthening business management in the field of marketing. MSME players are encouraged to have good knowledge management and absorptive capacity so that they are able to accumulate various information and knowledge absorbed from various information media in an effort to reach customers.